Collaborative engagement of Hispanic communities in the planning, conducting, and dissemination of assistive technology research - Elsa M. Orellano-Colón; Marta Rivero-Méndez; Claudia X. Boneu-Meléndez; Solymar Solís-Báez; Arelí León-Astor; Mariolga Juliá-Pacheco; María del Mar Santiago-Cruz; Jeffrey W. Jutai (Journal of Clinical and Translational Science, 2021)
Abstract